PENGELOLAAN PERBATASAN DARAT DI PROVINSI KALIMANTAN BARAT DARI PERSPEKTIF SOSIAL DAN EKONOMI PERTANIAN (Studi Kasus: Kecamatan Sanjingan Besar, Kabupaten Sambas) - Sihaloho, Henrykus (UNIKA Santo Thomas, 2012)
This study was a fisrst study when accompanying a working visitation of Special Committee of State Border of DPD RI (Senate of Republic of Indonesia) to East Borneo, West Borneo, and East Malaysia on March 29- April 2, 2011. This study concluded that poverty, stupidity, and underdevelopment were still a general phenomenon in borderland of West Borneo Province. There were two prominent perspective of Central Government on borderland area, namely ‘perception on economic benefit’ and ‘perception on sovereignty threat,’ causing policy and program doing to serve political and economic interest of Central Government and resulting marginalization the living of borderer through transmigration. Central Government construe the first perception as a economic benefit to Government and to transmigrant, not to local people, while the second perception construeing that the border area must be secured from the threats of the foreign country. This study also concluded that the borderland management needs three in one approach, that is combination of prosperity approach, security approach, and environment approach. The combination of three in one approach must stand on social and cultural reality because the borderland area was not homogenous and empty.